2022
DOI: 10.3324/haematol.2022.281442
|View full text |Cite
|
Sign up to set email alerts
|

ALK-negative anaplastic large cell lymphoma with <i>DUSP22</i> rearrangement has distinctive disease characteristics with better progression-free survival: a LYSA study

Abstract: ALK-negative anaplastic large cell lymphoma (ALCL) comprises subgroups harboring rearrangements of DUSP22 (DUSP22-R) or TP63 (TP63-R). Two studies respectively reported 90% and 40% 5-year overall survival (OS) in 21 and 12 DUSP22-R/TP63-not rearranged (NR) patients, making the prognostic impact of DUSP22-R unclear. Here, 104 newly diagnosed ALK-negative ALCL patients (including 37 from first-line clinical trials) from the LYSA TENOMIC database were analyzed by break-apart FISH assays for DUSP22-R and TP63-R. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…The study by Sibon and colleagues represents the largest series to date of 47 cases of DUSP22R ALK-negative ALCL derived from the TENOMIC database, a translational lymphoma research consortium of the LYSA group. In total, 47/104 (45%) cases harboured a DUSP22R which is significantly higher than other reports, and the authors acknowledge a selection bias as cases are submitted to the LYSA TENOMIC database with an aim of compiling those of clinical interest (13). In the subset enrolled on clinical trials, estimates are more in keeping with other studies (23-35%).…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…The study by Sibon and colleagues represents the largest series to date of 47 cases of DUSP22R ALK-negative ALCL derived from the TENOMIC database, a translational lymphoma research consortium of the LYSA group. In total, 47/104 (45%) cases harboured a DUSP22R which is significantly higher than other reports, and the authors acknowledge a selection bias as cases are submitted to the LYSA TENOMIC database with an aim of compiling those of clinical interest (13). In the subset enrolled on clinical trials, estimates are more in keeping with other studies (23-35%).…”
mentioning
confidence: 68%
“…The treatment landscape of ALCL has changed over the last decade with the approval of brentuximab vedotin (BV) in relapsed/refractory ALCL(15) and more recently, approval of CHP (cyclophosphamide, doxorubicin, prednisone)-BV in newly diagnosed systemic ALCL based on superior PFS and OS over CHOP, as shown in the ECHELON-2 study in CD30+ PTCLs (16). In the LYSA study, survival was notably poor from first relapse/progression, regardless of DUSP22R status suggesting that any prognostic relevance may diminish in this high risk setting (4 year OS 21%(DUSP22R) vs 34% (triple negative) P=0.62)(Figure 5A accompanying article) (13). The use of BV in relapsed/refractory ALCL improved outcome across genetic subgroups but similarly, there was no outcome difference noted.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…DUSP‐22 rearranged ALK‐ ALCL have a characteristic GEP signature characterized by downregulation of JAK/STAT pathway genes, global DNA hypomethylation, and an immunogenic phenotype 30,31 . In earlier reports, DUSP22 rearrangement was associated with a favorable prognosis with 5‐year OS rates of 40–90% equivalent to ALK+ ALCL, but recent studies including a large series from the LYSA group showed that higher risk groups with poor performance status had a 4‐year PFS and OS of only 17% and 21%, respectively 32,33 . The outcomes of DUSP‐22 rearranged ALCL are still improved compared with ALK‐ ALCL with TP63 rearrangements or triple‐negative ALCL lacking all 3 rearrangements.…”
Section: Molecular Pathogenesis Of Ptcl Subtypesmentioning
confidence: 99%